Job, career or calling: a qualitative exploration of the meaning of work among Brazilian undergraduate architecture students - Grillo, Pedro Moreira (2021)
Goal: To explore the relationship between different motivations and expectations and attributed meanings of work: as a job, career or calling. Design / Methodology / Approach: A survey with 82 undergraduate architecture and urbanism students was carried out, using with two seminal meaning of work questionnaires. Results were analyzed qualitatively. Results: (i) It is viable to analyze work as a job, career or calling; (ii) most of the interviewees (90%) faces work as something more than a job; (iii) It was shown that each subgroup has different motivations; (iv) It was also demonstrated that this subject is perceived as of great relevance for young people. Limitations of the investigation: Samples (size and subgroup) and qualitative analyses of the results were the major limitations. Therefore, bigger samples and different interviewees could increase validity of results. Practical implications: For organizations, the human resources department could add strategies about work perception on the employee hiring process. For individuals, the awareness of multiple meanings of work could be helpful in changing personal insights that influence careers and wellness. Originality / Value: The paper brings unprecedent approach and has some contributions to the field, such as: questionnaires translations and their use combined for the first time, besides the sample choice, which has also never been addressed before with this approach.